2022
DOI: 10.1001/jamaoncol.2021.7656
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Racial Disparity in Survival Outcomes for Early Hormone Receptor–Positive Breast Cancer After Adjusting for Insurance Status and Neighborhood Deprivation

Abstract: IMPORTANCE Racial disparities in survival outcomes among Black women with hormone receptor-positive breast cancer have been reported. However, the association between individual-level and neighborhood-level social determinants of health on such disparities has not been well studied.OBJECTIVE To evaluate the association between race and clinical outcomes (ie, relapse-free interval and overall survival) adjusting for individual insurance coverage and neighborhood deprivation index (NDI), measured using zip code … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“… 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Race is a social construct, 23 and observed differences in health experiences and outcomes by marginalized groups must be understood in the broader context of structural racism and other factors that differentially place minorities at increased risks for high symptom burden, enduring disparities in treatment adherence, and breast cancer outcomes. 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Race is a social construct, 23 and observed differences in health experiences and outcomes by marginalized groups must be understood in the broader context of structural racism and other factors that differentially place minorities at increased risks for high symptom burden, enduring disparities in treatment adherence, and breast cancer outcomes. 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
“…Differences in socioeconomic status, higher rates of exposure to environmental risk factors, lower access to health care, and explicit and implicit clinician bias driven by centuries of racism, oppression, and disinvestment, rather than biological differences, contribute to higher symptom burden among Black women . Race is a social construct, and observed differences in health experiences and outcomes by marginalized groups must be understood in the broader context of structural racism and other factors that differentially place minorities at increased risks for high symptom burden, enduring disparities in treatment adherence, and breast cancer outcomes …”
Section: Introductionmentioning
confidence: 99%
“…In the management of hormone receptor-positive individuals, endocrine therapy is extremely important. According to certain accounts, various hormone levels alter a patient’s prognosis ( 17 19 ). We found that upregulation of TIMM8A was inversely correlated with hormone receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that Black women are diagnosed at more advanced stages [28] and are more likely to discontinue chemotherapy [29]. Studies have reported that early discontinuation of therapy, clinicopathological characteristics, and insurance might not completely explain the survival differences between NHB and NHW women [9,30]. In a population study, Huang reported that patients with MBC in the lowest socioeconomic status (SES) quintile had a signi cantly increased risk of breast cancer death compared to those in the highest SES quintile (sHR 1.22, 95%CI 1.17-1.26).…”
Section: Discussionmentioning
confidence: 99%